2006
DOI: 10.1021/ie060340e
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Removal of SO2 and NO from Flue Gas with Calcium-Based Sorbent at Low Temperature

Abstract: The calcium-based sorbent for simultaneous removal of SO 2 /NO was prepared with KMnO 4 as additive. The activity of sorbent was studied individually in a fixed bed at low temperature. The experimental results showed that KMnO 4 could highly enhance the sorbent ability for NO capture. It was found that temperature rise could improve SO 2 capture, but could not influence NO removal so distinctively. The presence of water vapor in the gas could prominently improve the sorbent's ability to capture SO 2 and NO, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 10 publications
3
41
0
Order By: Relevance
“…The sorption capacity also increased with increasing RH from 115.8 mg/g to 131.5 mg/g. A similar report was presented by [20,21] over calcium based adsorbent, with SO 2 sorption increased with the addition of water vapor into the simulated flue gas [20,21]. Moreover water accumulating on the surface and interior pore of sorbent forms a liquid film which could make the reaction gas (SO 2 ), more easily absorbed by the sorbent rather than gas-solid reaction [22].…”
Section: Effect Of Relative Humidity (Rh)supporting
confidence: 67%
See 1 more Smart Citation
“…The sorption capacity also increased with increasing RH from 115.8 mg/g to 131.5 mg/g. A similar report was presented by [20,21] over calcium based adsorbent, with SO 2 sorption increased with the addition of water vapor into the simulated flue gas [20,21]. Moreover water accumulating on the surface and interior pore of sorbent forms a liquid film which could make the reaction gas (SO 2 ), more easily absorbed by the sorbent rather than gas-solid reaction [22].…”
Section: Effect Of Relative Humidity (Rh)supporting
confidence: 67%
“…A similar finding was reported for AC impregnated with V 2 O 5 [24], whereby in this work it was suggested that pore blockage was due to the by-products produced (ammonium-sulfate salts) during the reaction and the main reason for the unfavorable removal of NO at higher percentage of RH. Another similar finding reported a trend for NO removal with calcium based sorbent, and found the possible reason as surfacecatalyzed [20]. Therefore it can be concluded that when more water than necessary was on the sorbent surface, the water will foul the surface reaction.…”
Section: Effect Of Relative Humidity (Rh)mentioning
confidence: 70%
“…It is signicantly indicated that the emission cannot meet the new standard even the Claus tail gas is treated by the mentioned additional process. On this occasion, various absorption technologies, such as CaO, [16][17][18] MgO 19-21 and NH 3 (ref. [22][23][24] based desulfurization processes, are seriously considered as the potential candidate for Claus tail gas treatment due to the higher sulfur removal efficiency (can reach almost 100%) and low cost.…”
Section: 2mentioning
confidence: 99%
“…This process has a leading position on the current denoxing market. The drawbacks are its relatively high costs and poisoning of the catalyst by arsenic or alkali compounds in the fly ash [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These complexes, such as ferrous and cobalt chelates, can coordinate NO and be regenerated by different methods. Long et al pointed out that NO could be removed from exhausted gas streams by [Co(en) 3 ] 2+ (en=Ethylenediamine) or [Co(NH 3 ) 6 ] 2+ solution which could realize the oxidation and absorption of nitric oxide in the same reactor [14][15][16]. This process was superior to the method using Fe(II)-EDTA (EDTA=ethylenediamine-tetraacetate) solution because these cobalt chelates are substantially more resistant to oxidation than Fe(II)-EDTA [17].…”
Section: Introductionmentioning
confidence: 99%